2019
DOI: 10.3390/su11082295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vegetation Restoration on Soil Bacterial Communities, Enzyme Activities, and Nutrients of Reconstructed Soil in a Mining Area on the Loess Plateau, China

Abstract: Soil microbes are the main driving forces and influencing factors of biochemical reactions in the environment. Study of ecological recovery after mining activities has prompted wider recognition of the importance of microbial diversity to ecosystem recovery; however, the response of soil bacterial communities to vegetation restoration types and soil biochemical properties remains poorly understood. The purpose of this research was to explore the soil bacterial communities and soil biochemical properties at fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 51 publications
5
28
0
Order By: Relevance
“…The present study, land uses impacted on microbial biomass and generally increased in the order of degraded mine land < agricultural land < forest land, confirming our first and second hypothesis. This was consistent with other studies indicating that soil microbial biomass decreased when forested lands were converted to agricultural land or degraded by tillage implements [45,44].…”
Section: Soil Microbial Indicessupporting
confidence: 93%
See 1 more Smart Citation
“…The present study, land uses impacted on microbial biomass and generally increased in the order of degraded mine land < agricultural land < forest land, confirming our first and second hypothesis. This was consistent with other studies indicating that soil microbial biomass decreased when forested lands were converted to agricultural land or degraded by tillage implements [45,44].…”
Section: Soil Microbial Indicessupporting
confidence: 93%
“…The microbial biomass has been recognised as a key component of soil microbial activity influencing many soil processes [43]. They characteristically impact on soil quality thereby influencing the vegetation in a given area [44]. The microbial biomass is however, sensitive to environmental changes as well as land-use conversion.…”
Section: Soil Microbial Indicesmentioning
confidence: 99%
“…Among the bacteria from various topsoil sources, 92% belong to the 9 dominant phyla: Proteobacteria, Acidobacteria, Actinobacteria, Verrucomicrobia, Bacteroidetes, Chloroflexi, Planctomycetes, Gemmatimonadetes, and Firmicutes [ 31 ]. Li studied the effects of vegetation restoration among different soil bacterial communities, and the dominant phyla were Proteobacteria, Actinobacteria, and Acidobacteria [ 7 ]. Li [ 32 ] also investigated the diversity and composition of bacterial communities in response to reclamation of a soil subsidence area affected by mining activities, and found that the predominant phyla in present in the soils were Proteobacteria, Actinobacteria, Acidobacteria, and Planctomycetes.…”
Section: Discussionmentioning
confidence: 99%
“…Coal mining activities affect the physical quality of the soil: high bulk density and low water holding capacity, porosity, moisture content, pH, and soil nutrients (total nitrogen and available phosphorus) [ 6 ]. Coal mining activities interfered with the soil bacterial community structure, which led to a significant reduction in soil enzyme activity, with the dominant bacteria comprising Proteobacteria, Actinomycetes, and Acidobacteria [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors would like to make the following corrections about the published paper [1]. The changes are as follows:…”
mentioning
confidence: 99%